Why publish in Asian management journals? - YIU, Daphne W. (Institutional Knowledge at Singapore Management University, 2020)
Traditionally, region-focused journals are viewed as a secondary or second-tiered outlet for publications for marginalized research that carry a theme of a regional phenomenon and/or use regional data. Nonetheless, with the fast growth and increasing significance of Asian countries in the global economy, Asian management journals have recorded skyrocketing numbers of manuscript submissions and increasing impact factors in recent years. This chapter aims to provide a general discussion of the similarities and differences in publishing Asian research in Asian management journals compared with in North America as regards publication-related issues viewed and experienced by myself as author, reviewer and editor at Asian management journals in the past decade. I particularly use APJM as the focal Asian management journal in my illustrations. In addition, to echo the recent advocacy on the future direction of Asian management journals, I discuss if and how Asian management journals publish more indigenous research.